Dual reciprocity boundary node method for convection-diffusion problems. (July 2017) - Yan, Fei; Yu, Min; Lv, Jia-He
Abstract: This paper presents a dual reciprocity boundary node method(DHBNM) for steady-state convection-diffusion problems with variable velocities. In this formulation, the solutions are composed of a particular and a complementary solutions, where the former is solved by boundary node method, and the latter is obtained by dual reciprocity method(DRM). The velocity field is decomposed into an average and a perturbation ones, which is treated using DRM by some steps of approximating process. A reverse procedure for the particular solution is developed to overcome the difficulty of getting the analytical solution of the particular solution. Numerical studies have validated that the DHBNM can produce high accuracy and stability.